What Price the Moral High Ground? : How to Succeed without Selling Your Soul - Frank, Robert H. (Book collections on Project MUSE., 2004)
Financial disasters--and stories of the greedy bankers who precipitated them--seem to underscore the idea that self-interest will always trump concerns for the greater good. Indeed, this idea is supported by the prevailing theories in both economics and evolutionary biology. But is it valid? In What Price the Moral High Ground?, economist and social critic Robert Frank challenges the notion that doing well is accomplished only at the expense of doing good. Frank explores exciting new work in economics, psychology, and biology to argue that honest individuals often succeed, eve.